2012
DOI: 10.1002/hep.24744
|View full text |Cite
|
Sign up to set email alerts
|

The protease inhibitor, GS-9256, and non-nucleoside polymerase inhibitor tegobuvir alone, with ribavirin, or pegylated interferon plus ribavirin in hepatitis C

Abstract: Tegobuvir (GS-9190), a non-nucleoside nonstructural protein (NS)5B polymerase inhibitor, and GS-9256, an NS3 serine protease inhibitor, individually have activity against hepatitis C virus (HCV) genotype 1. The antiviral activity of tegobuvir and GS-9256 as oral combination therapy, or together with ribavirin (RBV) or pegylated interferon (Peg-IFN) alpha-2a and RBV, was assessed in a phase II, randomized, open-label trial. Treatmentnaïve patients with genotype 1 HCV were assigned 28 days of tegobuvir 40 mg twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 26 publications
(21 reference statements)
5
72
0
Order By: Relevance
“…The results of phase 1 and 2 studies involving patients with HCV genotype 1 infection have been encouraging and provide support for further development of combination therapies. [8][9][10][11][12][13] In the phase 1b Safety and Antiviral Effect of Oral Combinations without Interferon in Patients Diagnosed with Hepatitis C (SOUND-C1) study, patients who had not previously been treated for HCV infection received 4 weeks of treatment with faldaprevir (an NS3/4A protease inhibitor) and deleobuvir (formerly known as BI207127; a nonnucleoside inhibitor of nonstructural protein 5B [NS5B] polymerase) plus ribavirin. At week 4, 100% and 73% of patients who received faldaprevir plus ribavirin with 600 mg or 400 mg of deleobuvir, respectively, had HCV RNA levels that were lower than 25 IU per milliliter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of phase 1 and 2 studies involving patients with HCV genotype 1 infection have been encouraging and provide support for further development of combination therapies. [8][9][10][11][12][13] In the phase 1b Safety and Antiviral Effect of Oral Combinations without Interferon in Patients Diagnosed with Hepatitis C (SOUND-C1) study, patients who had not previously been treated for HCV infection received 4 weeks of treatment with faldaprevir (an NS3/4A protease inhibitor) and deleobuvir (formerly known as BI207127; a nonnucleoside inhibitor of nonstructural protein 5B [NS5B] polymerase) plus ribavirin. At week 4, 100% and 73% of patients who received faldaprevir plus ribavirin with 600 mg or 400 mg of deleobuvir, respectively, had HCV RNA levels that were lower than 25 IU per milliliter.…”
Section: Resultsmentioning
confidence: 99%
“…Enrollment in the TID28W-NR group was discontinued on February 3, 2011, at the request of the Food and Drug Administration after other studies showed that virologic breakthrough was more common with interferon-free regimens that did not contain ribavirin than with those that did. 13,17 Baseline demographic and clinical characteristics were similar in the five study groups (Table 1).…”
Section: Patientsmentioning
confidence: 89%
See 1 more Smart Citation
“…The molecular and physiological bases of the therapeutic activity of the current combination treatment with IFN-␣ plus ribavirin are poorly understood. It might be possible to establish new treatment protocols based on recently developed directly acting antiviral agents (DAAs), with or without IFN-␣ and ribavirin (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…NS5B RAVs conferring resistance to non-nucleoside NS5B inhibitors (such as dasabuvir or tegobuvir) are much more common than those involving nucleotide inhibitors, and are also associated with viral resistance and breakthrough. Overall, they are more common in genotype 1a than in genotype 1b (23), although variant C316N is more often seen in genotype 1b (24). RAV C316N/H/F has been identified at baseline in 6 patients with genotype 1b HCV who failed to respond to sofosbuvir, and in a patient with genotype 1a who later recurred; however, further studies are needed to appropriately establish the role of RAVs as a cause of resistance to sofosbuvir (25).…”
Section: Resistance-associated Variants (Ravs)mentioning
confidence: 99%